The same old story – or not? How storytelling can support inclusive local energy policy - Mourik, R. M.; Sonetti, G.; Robison, R. A. V. (Energy Research & Social Science, 2021)
Local energy policy agendas require commonly defined desirable future visions and collective agenda-setting to spur collaborative action. However, methods designed for multi-stakeholder engagement often do not sufficiently open up deliberative processes to all voices, and efforts to envision desired futures built from current local energy challenges are usually designed by and oriented towards specialists. With this paper, we aimed to explore how the theoretical strengths of storytelling for supporting local policy processes play out in practice. We contrast what the literature states about the potential of storytelling for solving complex challenges and facilitating collaborative processes to the lessons learnt from actually using storytelling in a set of 17 multi-stakeholder workshops across 17 European countries run as part of the H2020 SHAPE ENERGY project. The workshops were each designed around a tangible local energy policy challenge. We found storytelling has unique strengths in terms of enabling significant (un)learning regarding stakeholder relationships, allowing participants to step into others’ perspectives, keeping hold of diversity, and the use of ‘we’ in stories leading to concrete future initiatives. We also note specific learnings about when these outcomes may not be achieved, for example due to fears, traditions, hierarchical structures, as well as the need for sufficient time for planning, facilitator training and stakeholder invitations. We conclude that as an innovative, playful and flexible methodology, storytelling can undoubtedly be a valuable additional tool for policymakers where there is a desire for deliberative stakeholder involvement, and appetite to tailor approaches to local contexts.
Keywords: Changements climatiques; Engagement; Réservé UdeM; Vision collective